Reimagining pilocytic astrocytomas in the context of pediatric low-grade gliomas - Milde, Till; Rodriguez, Fausto J; Barnholtz-Sloan, Jill S; Patil, Nirav; Eberhart, Charles G; Gutmann, David H (Neuro-Oncology, 2021)
Pediatric low-grade gliomas (pLGGs) are the most common brain tumor in children and are associated with lifelong clinical morbidity. Relative to their high-grade adult counterparts or other malignant childhood brain tumors, there is a paucity of authenticated preclinical models for these pLGGs and an incomplete understanding of their molecular and cellular pathogenesis. While large-scale genomic profiling efforts have identified the majority of pathogenic driver mutations, which converge on the MAPK/ERK signaling pathway, it is now appreciated that these events may not be sufficient by themselves for gliomagenesis and clinical progression. In light of the recent World Health Organization reclassification of pLGGs, and pilocytic astrocytoma (PA), in particular, we review our current understanding of these pediatric brain tumors, provide a conceptual framework for future mechanistic studies, and outline the challenges and pressing needs for the pLGG clinical and research communities.
Gesehen am 15.01.2022